Geodiversity and Biodiversity of the Postglacial Landscape (Dębnica River Catchment, Poland) - Najwer, Alicja; Borysiak, Janina; Gudowicz, Joanna; Mazurek, Małgorzata; Zwoliński, Zbigniew (Quaestiones Geographicae, 2016)
The preparation of a proper zoning plan or landscape-ecological plan requires taking into account recognition of the natural values of an area covered by the plan and evaluating its abiotic and biotic diversities. The aim of the paper is to present the new approach to the procedure of geodiversity and biodiversity assessment. This procedure is used to characterise abiotic and biotic heterogeneity of the postglacial landscape modified by a man, tested on Dębnica River catchment (Western Pomerania, Poland). This catchment is a representative example illustrating the landscape of Central European Plain. The analytical algorithm of the geodiversity assessment is based on appropriate selection of the evaluation criteria: lithological, relative heights, landform fragmentation, hydrographical elements and mesoclimatic conditions. Biodiversity was assessed on the basis of real vegetation, potential natural vegetation and the degree of anthropisation of the natural vegetation with respect to syngenesis of plant associations. Seven factor maps were obtained: five for the diversity of abiotic elements, and two for the diversity of biotic elements, which became the basis for the creation of total geodiversity and biodiversity maps. Maps produced in accordance with given methodology may find a wide range of applications.